ANALYTICAL IMAGES OF POLITICAL TRUST IN TIMES OF GLOBAL CHALLENGES. THE CASE OF SLOVENIA, SPAIN AND SWITZERLAND - Coromina, Lluís; Kustec, Simona (Journal of comparative politics, 2020)
The main aim of this paper is to disentangle the understanding of political trust by analysing its determinants and trends in specific global crisis circumstances. Two fundamental perspectives of understandings of political trust as institutional and evaluation category in the period during the 2002 to 2012 are taken into focus, applying Switzerland, Spain and Slovenia as case study countries with different experiences of democratic development. The aim of the study is to see whether, and how, attitudes towards political trust in the three countries potentially changed during the set period and according to the set institutional and evaluation perspectives of political trust. A multiple group confirmatory factor analysis (MGCFA) and posterior structural equation model (SEM) are specified, applied on the European Social Survey (ESS) dataset. The study confirms that the perception of political trust is significantly divided within various types of political institutions. Attitudes to political trust in various democracies differ within political institutions depending on whether they exist at a national or international level, or whether they appear as individual political subject. Attitudes to political trust are also affected by time periods and global economic challenges. The findings point to the need for political institutions to perform in accordance with stable democratic patterns. Findings also point to the need for further research in order to track various prevailing characteristics of political trust in variously developed democracies.